Global prevalence of vasovagal syncope: a systematic review and meta-analysis - Salari, Nader; Karimi, Zohre; Hemmati, Mahvan; Mohammadi, Ali; Shohaimi, Shamarina; Mohammadi, Masoud (Elsevier, 2024)
Background: Today, vasovagal syncope is a common problem that has become a significant health and social challenge. The present study investigated the global prevalence of vasovagal syncope using a systematic review and meta-analysis. Methods: In this systematic review and meta-analysis study, the global prevalence of vasovagal syncope using the keywords Prevalence, Epidemiology, Vasovagal syncope, and Reflex syncope in PubMed, WoS, Scopus, ScienceDirect databases, and Google scholar search engine without time limit until July 20, 2022, was extracted and transferred to the information management software (EndNote). Then the repeated studies were excluded, and researchers evaluated the remaining studies during three stages (i.e., screening, eligibility, and qualitative assessment). The heterogeneity of studies was investigated using the I2 index, and the analysis of eligible studies was performed using the random effects model. Results: In the review of 12 studies with a sample size of 36,156 people, the global prevalence of vasovagal syncope was reported as 16.4 (95%CI: 6–37.5), and the study of publication bias in the studies through the Egger test shows the absence of publication bias in the studies. Conclusion: The prevalence reported in the studies shows a high prevalence of vasovagal syncope, which requires serious intervention and preventive, diagnostic, and therapeutic measures. It is necessary for health policymakers to take effective measures in this field.